2024
DOI: 10.3390/foods13071002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Flavonoid Chemical Structures and Their Antioxidant Capacity in Preventing Polycyclic Aromatic Hydrocarbons Formation in Heated Meat Model System

Thi Thu Huong Huynh,
Wanwisa Wongmaneepratip,
Kanithaporn Vangnai

Abstract: The relationship between the chemical structures of six flavonoids and their abilities to inhibit the formation of polycyclic aromatic hydrocarbons (PAHs) in a heated meat model system was investigated. The PAH8 forming in samples was analyzed by using QuEChERS coupled GC-MS. Inhibitory effects of PAHs were myricetin (72.1%) > morin (55.7%) > quercetin (57.3%) > kaempferol (49.9%) > rutin (32.7%) > taxifolin (30.2%). The antioxidant activities of these flavonoids, assessed through (1, 1-diphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The FRAP assay, utilized to assess the antioxidant potential of compounds or natural extracts, relies on the ability of antioxidative compounds to reduce TPTZ-Fe 3+ under acidic conditions, forming the stable ferrous form (TPTZ-Fe 2+ ), which exhibits maximum absorbance at 593 nm. The assay was conducted following the methodology outlined by Huong-Huynh et al in 2024 [49]. Fresh FRAP reagent was prepared by mixing 2.5 mL of a solution containing 10 mM TPTZ in 40 mM HCl with 2.5 mL of FeCl 3 .6H 2 O (20 mM) and 25 mL of acetate buffer (300 mM, pH 3.6).…”
Section: Frap Scavenging Testmentioning
confidence: 99%
“…The FRAP assay, utilized to assess the antioxidant potential of compounds or natural extracts, relies on the ability of antioxidative compounds to reduce TPTZ-Fe 3+ under acidic conditions, forming the stable ferrous form (TPTZ-Fe 2+ ), which exhibits maximum absorbance at 593 nm. The assay was conducted following the methodology outlined by Huong-Huynh et al in 2024 [49]. Fresh FRAP reagent was prepared by mixing 2.5 mL of a solution containing 10 mM TPTZ in 40 mM HCl with 2.5 mL of FeCl 3 .6H 2 O (20 mM) and 25 mL of acetate buffer (300 mM, pH 3.6).…”
Section: Frap Scavenging Testmentioning
confidence: 99%
“…Although the authors suggested that there was no correlation between the reduction of phenolic compounds and PAH8 production, more antioxidant analysis should be conducted before a conclusion is reached. In another study, it was suggested that ABTS could effectively demonstrate the correlation between the antioxidant properties of flavonoids and PAH formation . This indicates that the antioxidant properties of phytochemicals could be indicative of their capability to inhibit PAH formation.…”
Section: Intervention or Supplementation Of Phytochemicals Potentiall...mentioning
confidence: 99%
“…In another study, it was suggested that ABTS could effectively demonstrate the correlation between the antioxidant properties of flavonoids and PAH formation. 120 This indicates that the antioxidant properties of phytochemicals could be indicative of their capability to inhibit PAH formation. There are several mechanisms that have been pointed out to ameliorate circadian misalignment, but the involvement of AhR regulation was not mentioned.…”
Section: Intervention or Supplementation Of Phytochemicals Potentiall...mentioning
confidence: 99%
See 1 more Smart Citation